O-ODM Framework for Object-Relational Databases - Rombaldo Jr, Carlos Alberto; Alves Souza, Solange N; de Souza, Luiz Sergio (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2019)
Object-Relational Databases introduce new features which allow manipulating objects in databases.At present, many DBMS offer resources to manipulate objects in database, but most application developers just map class to relations tables, failing to exploit the O-R model strength. The lack of tools that aid the database project contributes to this situation. This work presents O-ODM (Object-Object Database Mapping), a persistent framework that maps objects from OO applications to database objects.Persistent Frameworks have been used to aid developers, managing all access to DBMS. This kind of tool allows developers to persist objects without solid knowledge about DBMSs and specific languages, improving the developers' productivity, mainly when a different DBMS is used. The results of some experiments using O-ODM are shown.
Keywords: Object-Relational Databases; persistence framework; java annotations; SQL:2008; IJIMAI